Nigeria-China Relations and Infrastructural Development in Nigeria - Ezeani, Emmanuel Onyebuchi; Ngoka, Ruth Obioma (University of Nigeria Journal of Political Economy, 2022)
The economies of the world have become greatly connected through globalization. Mutual benefits in forms of investments, technological and infrastructural developments, financial aids and the likes have driven many nation states to engage one another in relationships. Since the establishment of diplomatic relationship in 1971 between Nigeria and China, both countries have strived to explore available avenues to benefit from each other. The study analyses the impact of Nigeria-China relations on infrastructural development in Nigeria. The research is geared towards ascertaining if China’s investments in the energy sector enhanced sustainable energy transition in Nigeria and; to determine if China’s investment in the Belt and Road initiative led to transport infrastructure development in Nigeria. Documentary method of data collection was adopted for the study. Data were analysed using content analysis. The study adopted dependency theory as a theoretical framework. The findings revealed that China’s investment in the Nigerian energy sector has not birthed sustainable energy transition. However, China’s investment in the Belt and Road initiative has fostered rail and road transport infrastructure development in Nigeria though Nigeria still faces bottlenecks in her transport sector.